Analyzing the Effect of Employment in the Agricultural and Industrial Sectors on Economic Growth with the ARDL Bounds Test - DEMİR, Yıldırım (International Journal of Contemporary Economics and Administrative Sciences, 2021)
One of the important indicators determining the welfare level of a country is its Gross Domestic Product (GDP). However, many parameters affect GDP, and employment in agriculture and industry sectors constitute two of them. This study aims to determine the effect of employment in the agricultural and industrial sectors on economic growth in Turkey with the ARDL bounds test. Turkey’s employment rate in the agricultural and industrial sectors of the years 2000-2019 and GDP data were used as material. According to the ARDL model, it was determined that there is a long-term positive relationship between A_Employment and I_Employment and GDP. It was also observed that there was no structural break in the variables. With the Toda-Yamamoto test, a one-way causality relationship from A_Employment to GDP and a two-way causality relationship between S_ employment and GDP were determined. As a result, although about 20% of total employment in Turkey is in the agricultural sector labor productivity is quite low. This situation leads to an increase in the urban population and thus a decrease in employment in agriculture. Therefore, it is recommended that economic policies be developed to increase labor productivity in the agricultural sector.